Determinación del gen ApoE en pacientes con déficit cognitiva leve (Determination of ApoE gene in patients with mild cognitive impairment) - Román Garita, Norbel (Universidad de Costa Rica, 2014)
most common cause of dementia. It is a multifactorialdisease in which genetic and environmentalconditions interact to present a clinical manifestation.The e4 genotype for the apolipoprotein E(ApoE4) is a risk factor for developing AD.ApoE4 presents 15-16% of the general population,with greater presence in Caucasian populationsand nearly in 50% of subjects with AD.The presence of ApoE4 genotype increases the risk of developing AD 3 to 8 times higher and decreases age onset between 7 to 15 years. In homozygous form the risk increases 33 times. In late-onset AD is found in 65% of the cases and the percentage rises to 80% in presence of a family member with EA. ApoE remains the biomarker for predicting and diagnosing AD. Objective: To standardize the technique and determine the frequency of the ApoE’s 4 alleles of clinical significance in patients with mild cognitive impairment. Methods: Patients who were previously evaluated in the Memory Clinic- Hospital San Juan de Dios and diagnosed with mild cognitive impairment were selected. We collected blood samples and performed DNA extraction protocol by Miller et al. Multiplex PCR was performed in 14 patients for the simultaneous analysis of gene ApoE genotype of the samples. Results: We are testing a total of 14 patients diagnosed with mild cognitive impairment who were previously diagnosed by the interdisciplinary team to determine the presence of the ApoE gene. Conclusions: The frequency of the presence of the ApoE gene allows to describe the characteristics of the Costa Rican population as a risk factor for developing AD